2020
DOI: 10.7759/cureus.8047
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Ratio as a Prognostic Marker in Rectal Cancer Survival: A Systematic Review and Meta-Analysis

Abstract: The lymph node ratio (LNR) is defined as the ratio of the number of positive lymph nodes to the total number of nodes retrieved. LNR has recently emerged as a prognostic factor in rectal cancer. The objective of our study was to pool eligible studies to elucidate the prognostic role of LNR on overall survival (OS) and disease-free survival (DFS) in rectal cancer patients using a meta-analysis. Methods A systematic database search was performed in MEDLINE and Embase for relevant studies that reported LNR in rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…In recent times, LN ratio (LNR) is being evaluated as a prognostic indicator in several of the published studies apart from just using the number of positive LN [2][3][4][7][8][9][10][11][12][13][14][15][16][17][18]. The LNR is defined as the ratio of metastatic to the total number of harvested LNs, and it has emerged as an indicator of cancer-specific survival in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent times, LN ratio (LNR) is being evaluated as a prognostic indicator in several of the published studies apart from just using the number of positive LN [2][3][4][7][8][9][10][11][12][13][14][15][16][17][18]. The LNR is defined as the ratio of metastatic to the total number of harvested LNs, and it has emerged as an indicator of cancer-specific survival in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…The LNR is defined as the ratio of metastatic to the total number of harvested LNs, and it has emerged as an indicator of cancer-specific survival in recent years. The importance of LNR has been studied in various other solid malignancies and has been shown to be of significant prognostic value in rectal cancer survival in a recent meta-analysis [8].…”
Section: Introductionmentioning
confidence: 99%
“…This most common lymph nodal involvement occurs in up to 60%-70% of tongue cancers [14]. The total number of positive nodes has been recognized as a prognostic marker of adverse outcomes [15]. The OS benefit with LNM and the actuarial OS in patients without LNM is 95% and 71%, respectively [16].…”
Section: Discussionmentioning
confidence: 99%
“…In another study there was no significant difference in LNR value in patients with stage III rectal cancer regarding overall as well as diseasefree survival [91]. However, a recent systematic review using meta analysis has reported that a high LNR value is highly correlated with inferior overall survival and disease-free survival [90]. Although many studies have shown that LNR could be used as a prognostic tool for survival of rectal cancer patients, assessment of whether neoadjuvant chemo-radiotherapy impacts the lymph node ratio in patients with rectal cancer and LNR value in patients treated with neoadjuvant therapy affects the outcome of treatments, needs further evaluation.…”
Section: Lymph Node Ratiomentioning
confidence: 96%
“…The lymph node ratio (LNR), the ratio between the number of surgically removed metastatic and healthy lymph nodes, has been used as a prognostic marker in rectal cancer. Studies have shown that the LNR is an independent biomarker for survival in rectal cancer [87][88][89][90]. In one of the studies, 131 patients with rectal cancer were separated into two different groups based on the LNR value (≤0.2 [n = 86], > 0.2 [n = 45]) [87].…”
Section: Lymph Node Ratiomentioning
confidence: 99%